Frizzled-4 C-terminus Distal to KTXXXW Motif is Essential for Normal Dishevelled Recruitment and Norrin-stimulated Activation of Lef/Tcf-dependent Transcriptional Activation. (5th February 2016) - Bertalovitz, Alexander C.; Pau, Milly S.; Gao, Shujuan; Malbon, Craig C.; Wang, Hsien-yu
The carboxy (C)-termini of G protein coupled receptors (GPCR) dictate essential functions. The KTXXXW motif C-terminus of Frizzleds (FZD) has been implicated in recruitment of Dishevelled (DVL). Through study of FZD4 and its associated ligand Norrin, we report that a minimum of three residues distal to the KTXXXW motif in the C-terminal tail of Frizzled-4 are essential for DVL recruitment and robust Lef/Tcf-dependent transcriptional activation in response to Norrin.